Faster V̇O2 kinetics after priming exercises of different duration but same fatigue. Issue 10 (19th May 2018) - Mattioni Maturana, Felipe; Peyrard, Arthur; Temesi, John; Millet, Guillaume Y.; Murias, Juan M.
ABSTRACT: This study compared the responses of two priming exercises of similar fatigue on the adjustment of the oxygen uptake time constant (τV̇O2 ) in cycling. Ten healthy young adults (25 ± 3 yr) performed: three step transitions from a 20-W baseline to the power output (PO) below the gas exchange threshold (MOD, MODPRE ); a 3-min bout (P3MIN ) at 90% of peak PO (POpeak ), followed by MOD (MOD3MIN ); and a 6-min bout (P6MIN ) at 80% of POpeak, followed by MOD (MOD6MIN ). The O2  supply-to-O2 demand ([HHb]/V̇O2 ) ratio was calculated for MODPRE, MOD3MIN, and MOD6MIN . Neuromuscular fatigue was measured isometrically pre- and post-priming exercise. Reductions in maximal voluntary contraction (−29 ± 6 vs −34 ± 7%) and high-frequency doublet amplitude (−48 ± 13 vs −43 ± 11%) were not significantly different between P3MIN vs P6MIN, suggesting similar fatigue. τV̇O2 for MOD3MIN and MOD6MIN were similar, being ~25% smaller than MODPRE . The [HHb]/V̇O2 ratio was significantly greater in MODPRE (1.13 ± 0.12) compared to MOD3MIN (1.02 ± 0.04) and MOD6MIN (1.02 ± 0.04). This study showed that priming exercise of shorter duration and higher intensity, was sufficient to accelerate V̇O2 kinetics similarly to that observed subsequent to P6MIN when the muscle fatigue was similar.